A new dynamic prioritization technique for web application regression testing - Nejad, Mojtaba Raeisi Dobuneh (2015)
Web applications have served as critical tools for different business. Failure of these critical tools means the loss of millions of dollars for the organizations that are using them. Most web applications must run without any interruption day and night. This requires testers to isolate the software bugs and software engineers to fix them immediately and release new versions. The fixing of bugs in web applications requires a short time span so the test cases can help the testers best in detection of new faults during the testing phase. Regression test aims at generating test cases that can detect behavioral differences between the original and the modified versions of a program. Prioritization is recent approach for regression testing has been used for testing web application aims to run test cases with the order to find faults in earlier time. In this research, dynamic approaches are applied based on criteria related to log file which are collected from database of server side. Knowledge analysis workbench is determined the best combination of test cases by set the dynamic weighting of the criteria.